Expressing diminutive meaning in heritage Spanish: linking the heritage experience to diminutive use in everyday speech - Cruz, Abel (Frontiers in Language Sciences, 2024)
This paper studies the pragmatic force that heritage speakers may convey through the use of the diminutive in everyday speech. In particular, I analyze the use of the Spanish diminutive in 49 sociolinguistic interviews from a Spanish–English bilingual community in Southern Arizona, U.S. where Spanish is the heritage language. I compare the use of the diminutive in heritage Spanish to the distribution of the diminutive in the speech of a Spanish monolingual community (18 sociolinguistic interviews) from the same dialectal region. Although Spanish and English employ different morphosyntactic strategies to express diminutive meaning, the analysis reveals that the diminutive morpheme -ito/a is a productive morphological device in the Spanish-discourse of heritage speakers from Southern Arizona (i.e., similar diminutive distributions to their monolingual counterparts). While heritage speakers employed the diminutive -ito/a to express the notion of ‘smallness’ in their Spanish-discourse, the analysis indicates that these language users are more likely to invoke a subjective evaluation through the diminutive -ito/a when talking about their family members and/or childhood experiences. This particular finding suggests that the concept ‘child’ is the semantic/pragmatic driving force of the diminutive in heritage Spanish as a marker of speech by, about, to, or with some relation to children. The analysis further suggests that examining the pragmatic dimensions of the diminutive in everyday speech can provide important insights into how heritage speakers encode and create cultural meaning in their heritage languages.